Keratinase production and biodegradation of polluted secondary chicken feather wastes by a newly isolated multi heavy metal tolerant bacterium-Alcaligenes sp AQ05-001 - Yusuf, I; Ahmad, SA; Phang, LY; Syed, MA; Shamaan, NA; Khalil, KA; Dahalan, FA; Shukor, MY (Academic Press Ltd- Elsevier Science Ltd, 2024)
Biodegradation of agricultural wastes, generated annually from poultry farms and slaughterhouses, can solve the pollution problem and at the same time yield valuable degradation products. But these wastes also constitute environmental nuisance, especially in Malaysia where their illegal disposal on heavy metal contaminated soils poses a serious biodegradation issue as feather tends to accumulate heavy metals from the surrounding environment. Further, continuous use of feather wastes as cheap biosorbent material for the removal of heavy metals from effluents has contributed to the rising amount of polluted feathers, which has necessitated the search for heavy metal-tolerant feather degrading strains. Isolation, characterization and application of a novel heavy metal-tolerant feather-degrading bacterium, identified by 16S RNA sequencing as Alcaligenes sp. AQ05-001 in degradation of heavy metal polluted recalcitrant agricultural wastes, have been reported. Physico-cultural conditions influencing its activities were studied using one-factor-at-a-time and a statistical optimisation approach. Complete degradation of 5 g/L feather was achieved with pH 8, 2% inoculum at 27 degrees C and incubation period of 36 h. The medium optimisation after the response surface methodology (RSM) resulted in a 10-fold increase in keratinase production (88.4 U/mL) over the initial 8.85 U/mL when supplemented with 0.5% (w/v) sucrose, 0.15% (w/v) ammonium bicarbonate, 03% (w/v) skim milk, and 0.01% (w/v) urea. Under optimum conditions, the bacterium was able to degrade heavy metal polluted feathers completely and produced valuable keratinase and protein-rich hydrolysates. About 83% of the feathers polluted with a mixture of highly toxic metals were degraded with high keratinase activities. The heavy metal tolerance ability of this bacterium can be harnessed not only in keratinase production but also in the bioremediation of heavy metal polluted feather wastes. (C) 2016 Published by Elsevier Ltd.